2016
DOI: 10.1080/08961530.2015.1082080
|View full text |Cite
|
Sign up to set email alerts
|

Smart grocery shopper segments

Abstract: This study segments grocery shoppers seeking to maximize shopping value and minimize the investment of time, money, and effort. The literature lacks investigations of grocery shoppers based on shopping activities; therefore, this study aims to fill the gap. Data were obtained from 751 respondents who recently made a smart grocery shopping purchase. The cluster analysis to segment grocery shoppers yielded three types: spontaneous smart shoppers, apathetic smart shoppers, and involved smart shoppers. The segment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 39 publications
(59 reference statements)
1
21
0
Order By: Relevance
“…The most frequently and strongly observed discriminating factors were: shopping convenience (Atkins et al, 2016;Ganesh et al, 2010;Rohm and Swaminathan, 2004) (Harris et al, 2017a); time consciousness and pressures (Atkins et al, 2016;Harris et al, 2017a;Mokhtarian et al, 2009;Williams et al, 2015); price consciousness (Atkins et al, 2016;Ganesh et al, 2010;Mokhtarian et al, 2009); innovativeness (Konuş et al, 2008;Wang et al, 2014); shopping enjoyment (Konuş et al, 2008;Mokhtarian et al, 2009;Williams et al, 2015); use of information (Atkins et al, 2016;Rohm and Swaminathan, 2004;Williams et al, 2015); and variety seeking (Atkins et al, 2016;Ganesh et al, 2010;Rohm and Swaminathan, 2004).…”
Section: Choice Of Discriminating Factorsmentioning
confidence: 99%
“…The most frequently and strongly observed discriminating factors were: shopping convenience (Atkins et al, 2016;Ganesh et al, 2010;Rohm and Swaminathan, 2004) (Harris et al, 2017a); time consciousness and pressures (Atkins et al, 2016;Harris et al, 2017a;Mokhtarian et al, 2009;Williams et al, 2015); price consciousness (Atkins et al, 2016;Ganesh et al, 2010;Mokhtarian et al, 2009); innovativeness (Konuş et al, 2008;Wang et al, 2014); shopping enjoyment (Konuş et al, 2008;Mokhtarian et al, 2009;Williams et al, 2015); use of information (Atkins et al, 2016;Rohm and Swaminathan, 2004;Williams et al, 2015); and variety seeking (Atkins et al, 2016;Ganesh et al, 2010;Rohm and Swaminathan, 2004).…”
Section: Choice Of Discriminating Factorsmentioning
confidence: 99%
“…In line with the past studies, survey data were applied for the analysis [ 4 , 74 , 75 ]. Based on the analysis results, each cluster is given a label that best describes its defining features [ [76] , [77] , [78] , [79] ].…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Studies in developed markets point to proximity of stores affected shopping patterns and store choices (Fox et al, 2004), age, education and occupation influence consumer perceptions of price, promotions and cleanliness at grocery stores (Mortimer and Clarke, 2011), gender, age of children, middle-class families with educated parents influence grocery purchase decisions (Haselhoff et al, 2014), distance and store accessibility, purchase frequency, shopping orientation influence grocery buying behavior (Nilsson et al, 2015a), gender and money spent influences store-attributes ratings (Nilsson et al, 2015b), and smart grocery shopper segments vary across generational cohorts (Atkins et al, 2016).…”
Section: Store-attributes: Developed Vs Emerging Marketsmentioning
confidence: 99%
“…In India, although organized retail occupies about 8% of the total retail industry, the F&G segment accounts for 66 per cent of the total revenues of the retail industry (IBEF, 2017), indicating the scope of growth in food retailing. Incidentally, studies in developed markets have shown how food retailing can be explored profitably by focusing on store and productattributes (Cicia et al, 2002;Carpenter and Moore, 2006;Olsen and Skallerud, 2011;Mortimer and Clarke, 2011;Nilsson et al, 2015b;Migliore et al, 2015;Atkins et al, 2016). Similarly, in India, food retailing studies report on evolving consumer dynamics and modernization of food retail that have contributed to the growth in this sector (Ali et al, 2010;Prasad and Aryasri, 2011;Dutta et al, 2016).…”
Section: Introductionmentioning
confidence: 99%